Development of a Control and Monitoring System for Ballast Systems Based on Programmable Logic Controllers (PLC) and Human-Machine Interface (HMI) - Arifin, Mohammad Danil; Oloan, Aldyn Clinton Partahi; Brahmantyo, Esaricko Herli (Institut Teknologi Sepuluh Nopember, 2025)
The ballast control management system plays a vital role in maritime operations by ensuring vessel stability and safety while minimizing environmental risks associated with ballast water transfer. Effective ballast management regulates the filling and emptying of ballast tanks to maintain proper trim, draft, and balance during navigation and docking. With the enforcement of the Ballast Water Management (BWM) Convention by the International Maritime Organization (IMO), vessels must implement a Ballast Water Management Plan (BWMP) and maintain a Ballast Water Record Book to comply with international regulations. This study aims to develop a PLC- and HMI-based ballast control system that enhances monitoring and automation of ballast operations. The system is designed to improve control accuracy, diagnostic capabilities, and operational flexibility while ensuring compliance with IMO regulations. The research methodology involves system design, hardware integration, and software programming to create an automated control and monitoring solution. The PLC system utilizes digital inputs to operate pumps and valves, while analog sensors measure tank levels and pressure. The HMI interface displays real-time data, enabling seamless user interaction. The results demonstrate that the proposed system significantly enhances ballast operations by improving automation, control accuracy, and monitoring capabilities. The system ensures safe and efficient ballast management while facilitating regulatory compliance. These findings highlight the potential of PLC and HMI technologies in advancing maritime automation and control systems.